2016
DOI: 10.7161/anajas.2016.31.1.40-59
|View full text |Cite
|
Sign up to set email alerts
|

İstanbul ilinde tıbbi, aromatik ve baharat bitkileri satışı yapan aktarların yapısal özellikleri ve mevzuat hakkındaki görüşleri

Abstract: ÖZETBu araştırmada, İstanbul İlindeki aktarların yapısal özellikleri ve faaliyetleri ile ilgili mevzuat hükümleri hakkındaki görüşlerinin belirlenmesi amaçlanmıştır. Veriler, 2015 yılının Ocak ayında ildeki 75 aktardan anket yoluyla sağlanmıştır. Metot olarak, yüzde dağılım ve ortalamaların yanında denetimleri yeterli ve etkin bulma durumu ile aktarların bazı özellikleri arasındaki ilişkiyi belirlemek için Khi-kare (X 2 ) testi ve aktarların mevzuat hükümlerine ilişkin görüşlerini tespit etmek amacıyla Faktör … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
1
3
0
6
Order By: Relevance
“…Educational status is the most high school graduate with a rate of 43.63%, 30.90% primary, 16.36% secondary and 9.11% are university graduates (Figure 7). Among other researches that are similar to our study [35,48,42,49,50] .…”
Section: Resultssupporting
confidence: 89%
“…Educational status is the most high school graduate with a rate of 43.63%, 30.90% primary, 16.36% secondary and 9.11% are university graduates (Figure 7). Among other researches that are similar to our study [35,48,42,49,50] .…”
Section: Resultssupporting
confidence: 89%
“…Other studies performed in Turkey by Başer et al. (1986) , Adıgüzel and Kızılaslan (2016) , Akbulut (2015) reported that most herbalists in have low educational levels. Our interviews also indicated that only one herbalist received a university education related to medicinal and aromatic plants; in contrast, the other herbalists learned from masters or were self-taught.…”
Section: Resultsmentioning
confidence: 89%
“…P. tomentosa'nın en iyi sitotoksik etkiyi hekzan ekstresinde gösterdiği tespit edilmiştir. (Adıgüzel and Kızılaslan, 2016). Especially with the increasing number of chronic diseases, the importance of the drug used in treatment, the amount of the drug and the desired physiological response have increased the use of herbal medicine in the World (Doğan & Avcı, 2018).…”
Section: Antimicrobial Effect Antioxidant Effect Cytotoxic Effectmentioning
confidence: 99%